JUAL BELI TANAH HAK MILIK BERDASARKANPERJANJIAN NOMINEE (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 1290K/PDT/2022): Sale and Purchase Freehold Land Based on Nominee Agreement (Study on Supreme Court’s Verdict Number 1290K/Pdt/2022) - Christiangie, Merry; Sumanto, Listyowati (AMICUS CURIAE, 2024)
Land sale and purchase is an act of transferring land rights between the seller and the buyer with the payment of the agreed price by the buyer to the seller is carried out simultaneously which is cash, clear, and real. Sale and purchase of land with the status of Property Rights can only be carried out between fellow Indonesian citizens or legal entities designated by Government Regulation Number 38 of 1963.The formulation of this research problem is regarding the validity of the sale and purchase of freehold land based on a nominee agreement in the Supreme Court Decision in terms of Law Number 5 of 1960 concerning Basic Agrarian Principles and the suitability of the judge's consideration with the Basic Agrarian Law in Supreme Court Decision Number 1290K/Pdt/2022 so that the freehold land belongs to Dodi Usman. The research method used in this research is normative juridical research using secondary data analyzed qualitatively, and drawing conclusions using deductive logic. In Indonesian positive law, the Nominee Agreement is a prohibited agreement. The sale and purchase of land with the status of HakMilik based on a nominee agreement is invalid because it violates the provisions of Article 26 paragraph (2) of the UUPA which results in legal smuggling, and violates the Minister of Home Affairs Instruction No.14 of 1982 concerning the Prohibition of the Use of Absolute Power of Attorney as a Transfer of Land Rights because of the granting of absolute power of attorney by Dodi Usman to Marc van Loo.